Effect of Forest Tree Species on the Yield Potential of Intercrops - Maheta, K. B.; Kukadia, M. U.; Vashi, B. G.; Jadeja, D. B. (Indian Forester, 1996)
The present investigation was carried out with its prime objective to study the effect of forest tree species on the yield potential of inter crops during the year 1994-95. Grain yield of agricultural crops (intercrops) grown in association with trees decreased compared to sole crops. The reductions in yields under Casuarina were more than Adina cordifolia and Gmelina arborea. Maumum light intensity was recorded under open field (control) wbile it was found to he minimum with Casuarina.